Government Policy Strategy in Optimizing MSME Empowerment at the Bulak Fish Market Center in Surabaya - Muhammad Chasan Amrulloh; Rumanintya Lisaria Putri; Joko Sutrisno; Eko Wahyono (Journal of Governance and Public Policy, 2023)
The Bulak fish market center is one of the fish markets for MSMEs players who utilize marine resources in describing the urgency of government policy for MSMEs which are the backbone of the national economy due to being affected by aspects of production. This study used descriptive qualitative research with data collection techniques through observation, interviews, documentation and previous research. The results showed that government policies are still not fully implemented in optimizing the empowerment of MSMEs in Bulak fish market centers. The government can optimize it to facilitate MSME actors so that the quality and products produced can be piloted in every region in Indonesia. This study used descriptive qualitative research with data collection techniques through observation, interviews, documentation and previous research. Government policies are still not fully implemented in optimizing the empowerment of MSMEs in Bulak fish market centers. The government can optimize it to facilitate MSME actors so that the quality and products produced can be piloted in every region in Indonesia.